Borderline Personality Disorder in Patients With Medical Illness: A Review of Assessment, Prevalence, and Treatment Options. Issue 7 (September 2019) - Doering, Stephan
ABSTRACT: Objective: Borderline personality disorder (BPD) occurs in 0.7% to 3.5% of the general population. Patients with BPD experience excessive comorbidity of psychiatric and somatic diseases and are known to be high users of health care services. Because of a range of challenges related to adverse health behaviors and their interpersonal style, patients with BPD are often regarded as "difficult" to interact with and treat optimally. Methods: This narrative review focuses on epidemiological studies on BPD and its comorbidity with a specific focus on somatic illness. Empirically validated treatments are summarized, and implementation of specific treatment models is discussed. Results: The prevalence of BPD among psychiatric inpatients (9%–14%) and outpatients (12%–18%) is high; medical service use is very frequent, annual societal costs vary between [Euro sign]11, 000 and [Euro sign]28, 000. BPD is associated with cardiovascular diseases and stroke, metabolic disease including diabetes and obesity, gastrointestinal disease, arthritis and chronic pain, venereal diseases, and HIV infection as well as sleep disorders. Psychotherapy is the treatment of choice for BPD. Several manualized treatments for BPD have been empirically validated, including dialectical behavior therapy, transference-focused psychotherapy, mentalization-based therapy, and schema-focused therapy. Conclusions: Health care could be substantially improved if all medical specialties would be familiar with BPD, its pathology, medical and psychiatric comorbidities, complications, and treatment. In mental health care, several empirically validated treatments that are applicable in a wide range of clinical settings are available.